Hubungan Antara Dukungan Sosial dengan Psychological Well Being pada Guru Honorer Daerah - Nugraheni, Agi Septina, Dra. Wiwien Dinar Prastiti, M.Si (2016)
Someone who has a high psychological well being will feel comfortable, peaceful, and always happy. a honorary teacher need of social support from the surrounding environment in order to be fulfilled psychological well being. This research aims to knowing the relationship between social support and psychological well being on a honorary teacher area. The method of collecting data using a scale of psychological well being and social support scale were then analyzed using product moment correlation. Results of data analysis obtained correlation coefficient (r) is 0.395 with significance level is 0.005 (p <0.01) means that there is a significant positive relationship between psychological well being and social support. Effective contribution of social support and psychological well being is 59,84 and (RH) is 47.5 which shows the high category. While social support variables have (RE) is 108.62 (RH) is 85 which indicates the high category. The conclusion from this study is that there is a positive relationship between social support and psychological well being.